Alterations in pain during adolescence and puberty. Issue 4 (April 2023) - Nahman-Averbuch, Hadas; Li, Rui; Boerner, Katelynn E.; Lewis, Christopher; Garwood, Sarah; Palermo, Tonya M.; Jordan, Abbie
Highlights: Adolescence is characterized by several changes in both clinical and experimental pain, including a decrease in experimental pain sensitivity, an increase in the new onset of chronic pain syndromes, and the emergence of sex differences in pain. Biological changes such as an increase in sex hormone levels and changes in brain structure and function, which are related to puberty or transition to adulthood, can contribute to the alterations in pain. Changes in psychological factors, including identity formation, gendered influences, and possible development of anxiety and depression, can be related to pain alterations during adolescence. Social changes during adolescence, including increased reliance on peer relationships and an increase in family conflict, can impact pain experiences. The relationships between biopsychosocial changes and pain alterations during adolescence may be bidirectional. Abstract: During adolescence and puberty, alterations in pain, both experimental and clinical, are observed. In addition, adolescents undergo extensive biopsychosocial changes as they transition from childhood to adulthood. However, a better understanding of how the biopsychosocial changes during adolescence impact pain is needed to improve pain management and develop targeted pain interventions for adolescents. This review synthesizes the literature on alterations in pain during adolescence in humans, describes the potential biopsychosocial factors impacting pain during adolescence, and suggests future research directions to advance the understanding of the impact of adolescent development on pain.